ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI PROGRAM LINEAR - Handayani, Restu (Departemen Matematika, 2023)
The purpose of this research is to find out the level of students' mathematical communication abilities. The type of research used is qualitative research with a descriptive approach. The stages in this study were divided into the preparation, implementation and analysis stage. The instrument used is a test in the form of essay questions which contain indicators of mathematical communication ability. This research was conducted in class XI IPS MAN 2 Kota Padang. The results showed that the level of mathematical ability in class XI IPS 2 MAN 2 Padang City was low especially in Linear Program material, which is caused by a lack of understanding related to Linear Program.Keywords: Analysis of Student’s Mathematical Ability, Communication Mathematical Ablitiy, Linear Program